CHARACTERIZATION OF BANGKA ISLAND GRANITOID BASED ON SPECTROSCOPY GEOCHEMICAL ANALYSES - SETIAWAN WIDANA (NIM : 22010002); Pembimbing : Dr. Ir. Bambang Priadi, KURNIA
Klabat granite compiled by variations of granitoid in Bangka Island. This study aims to investigate the characteristics of granitoid Bangka Island to be applied in the study of magmatism, tectonic situations and relationships developed in granitoid for possible exploration. The methodology used by geochemical spectroscopic observations with a thin section of rock (petrography). Spectroscopic methods technique by Neutron Activation Analysis (NAA) and X-Ray Fluorescence (XRF). The elements analyzed were trace and rare earth elements. Irradiated samples conducted at the Center for Multipurpose Reactor "Siwabessy", BATAN-Serpong. Granitoid sampel from Western, Southern, Central and East (Belinyu). Granitoid ages range from Late Permian to Late Triassic. Petrographic analysis of the results showed granitoid type and dominant as Alkali Feldspar - Syeno Granite, whereas geochemical analysis as Alkali -Syeno Granite. SiO2 variation diagram shows the decline in the proportion of the major elements CaO, MgO, TiO2, Al2O3 and P2O5 with increasing SiO2 influenced by affinity fractionation as calc-alkalic magma with high K content. Affinity can be formed on continental margins where subduction and collision involve. In commoml granitoid typology as peraluminous, with type I in Central and Eastern Bangka granitoid (Belinyu) characterized high proportion of magnetite and Y, while type S in the South and West Bangka granitoids are characterized by high K2O and the presence of abundant biotite. Plotting in a spider diagram normalized to chondrite shows LILE against HFSE enrichment, depletion consistent except Nb, and LREE enrichment relative to flat HREE. The condition shows the character of subduction-related continental arc, whereas Rb abundance indicates the position of Syn Collision. The tectonic conditions affect the formation of granitoid magmatism Bangka Island. Trace elements ratios indicate the source of magmatism in Central and Eastern Bangka (Belinyu) as shosonitik (mixed), while the South and West Bangka as the crust. It also distinguishes tectonomagmatism respectively as subduction and collision influenced. Granitoid magmatism formed due to subduction of Central Bangka and Belinyu the Late Permian-Early Triassic along with the closure of Paleo-Tethys due to the merger of Malaya Block Sibumasu and East, while the Middle Triassic - Late collision with the West Sumatra Block Sibumasu produce granitoid South and West Bangka-influenced crust.